Monialaisten maatilayritysten taloudelliset tulokset - Kaila, Minna-Mari (Maatalouden taloudellinen tutkimuslaitos, 1998)
Maatiloilla, joilla on monialaista yritystoimintaa, on voitu lisätä käytettävissä olevaa tuloa ja parantaa nettotulosta. Tulokset vuodelta 1996 perustuvat 40 sellaisen maatilan kirjanpitoon, joilla on maatalouden ohella myös yhtä tai useampaa muuta yritystoimintaa. Nämä tilat ovat maatiloina yleensä pienehköjä. Pääasialliset muut toimialat olivat koneurakointi, elintarvikkeiden jatkojalostus, puun jatkojalostus ja maatilamatkailu. Nettotuloksella mitattuna parhaiten näytti kannattavan puun jatkojalostus. Monialaisten maatilayritysten talousseuranta on toistaiseksi ollut kovin vähäistä. Maaseudun kehittämisen näkökulmasta seurannan laajentaminen ja eri toimialojen kattavuuden lisääminen on erittäin tarpeellista.

This article is concerned with pluriactive farm enterprises, i.e. farms practising other entrepreneurial activities besides traditional agricultural production, and the benefits obtained from such pluriactivities. The objective is to find out whether pluriactivity has improved the profitability of the farm enterprise. The study is based on data from the profitability bookkeeping of farm enterprises, and the reference data concerning agriculture consists of results from the FADN farms. The profitability bookkeeping of pluriactive farm enterprises was started in 1996, and in the first year 40 farms participated in the bookkeeping. The article concerning the economy of pluriactive farm enterprises deals with machine contracting, wood processing, farm holidays and processing of agricultural products as separate branches of industry, and the profitability of these has been compared with that of traditional farm enterprises. According to the results of 1996, the profitability of pluriactive farm enterprises was weaker than that of traditional farms. However, on the basis of the financial statements of one single year no direct conclusions concerning the unprofitability of pluriactivity can be made. The area of the pluriactive farms participating in the bookkeeping was smaller than on the traditional farms, and thus the income from agriculture only would also very likely have been smaller than in the reference group.
Economic results of pluriactive farm enterprises
Keywords: Ma; maataloustulo; monialayritykset; kirjanpitotilat; farm income; farm results; bookkeeping; pluriactive farms